The global burden and trends analysis of early-onset colorectal cancer attributable to dietary risk factors in 204 countries and territories, 1990–2019: a secondary analysis for the global burden of disease study 2019 - Su, Jiao; Liang, Yuanhao; He, Xiaofeng (Frontiers in Nutrition, 2024)
Background Rising trends in early-onset colorectal cancer (CRC) burden have been observed, but the distribution and temporal patterns of early-onset CRC attributable to dietary risks remain unclear. Objectives This study aimed to estimate the burden of early-onset CRC attributable to dietary risk factors globally, regionally, and nationally, by age and sex, from 1990 to 2019. Methods The absolute number and age-specific rates (ASR) of diet-related early-onset CRC burden, as well as summary exposure value (SEV) of attributable dietary risk factors, were extracted from the Global Burden of Disease (GBD) Study 2019. The temporal changes in the burden between 1990 and 2019 were analyzed by calculating the percentage change in the absolute number of burden and the estimated annual percentage change (EAPC) in ASR of burden. The annualized rates of change (ARC) were calculated to evaluate the variation trend of SEV. Results In 2019, diet-related early-onset CRC caused 30,096 (95% UI: 23,148 to 36,091) death cases and 1,465,755 (95% UI: 1,126,489 to 1,761,661) DALYs worldwide, accounting for 34.8% deaths and 34.4% DALYs of overall early-onset CRC, respectively. Moreover, a diet low in milk (responsible for 16.5% [95% UI: 11.1 to 21.9%] of DALYs in 2019), low in whole grains (15.2% [95% UI: 5.9 to 19.9%]), low in calcium (14.3% [95% UI: 10.7 to 18.9%]), high in red meat (5.3% [95% UI: 1.7 to 9.5%]), high in processed meat (2.5% [95% UI: 0.9 to 4.0%]), and low in fiber (2.3% [95% UI: 0.9 to 4.2%]) were early-onset CRC attributable dietary risk factors. The age-specific DALYs rate of early-onset CRC attributable to each dietary risk factor generally showed an increasing trend globally between 1990 and 2019, except for low intake of fiber (EAPC = −0.57, 95% CI: −0.76 to −0.38). In addition, from 1990 to 2019, males have a higher burden than females and this gap may continue to widen due to the increasing difference between the sexes in most dietary risk factors. Furthermore, dietary risks-attributable early-onset CRC burden has shifted from regions with high socio-demographic index (SDI) to high-middle and middle SDI quintiles with uncontrolled dietary risks. Conclusion Early-onset CRC remains a concerning issue globally, and effective prevention and modification of dietary risk factors holds great promise to reduce early-onset CRC-related burden. Prioritizing diet improvement for males is critical and urgent for CRC control efforts, particularly for those living in developing countries with ongoing dietary pattern transition.